The effectiveness of transdermal iron patches in athletes with suboptimal iron status (Part 1) - McCormick, R.; Dawson, B.; Sim, M.; Lester, L.; Goodman, C.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Dietary intake alone is often insufficient to fulfill the iron demands of an athlete. This issue has manifested in the ongoing high rates of iron deficiency (ID) among male (~3% to 11%) and female (~15% to 35%) athletes (Sim et al., 2019). Symptoms of ID include lethargy, fatigue, and, in more severe cases, reduced work capacity (Haas & Brownlie, 2001), which may impede training and performance outcomes in athletes. Iron balance is a challenge for athletes because they encounter additional mechanisms of iron loss during exercise, including sweating, hematuria, gastrointestinal (GI) bleeding, and hemolysis (Peeling et al., 2008). Negative iron balance ensues when athletes consume a suboptimal amount of dietary iron to counteract these losses. In addition, these losses can be difficult to restore due to the low bioavailability of dietary iron (15-35% for heme and 2-20% for nonheme; Craig, 1994) and the inability to endogenously replenish taxed iron stores (Sim et al., 2019). Furthermore, recent research has identified a link between exercise-induced inflammation and an increase in the primary iron regulatory hormone, hepcidin. Hepcidin is reported to peak at 3 hr and remain elevated for 6 hr postexercise, and is linked to suppressed dietary iron absorption and recycling by duodenal enterocytes and macrophages, respectively (Nemeth et al., 2004; Peeling et al., 2009). Therefore, athletes will often need to consider supplemental sources of iron, beyond dietary sources, to achieve healthy iron status.